Answers

2015-07-28T22:22:49+05:30
Let  \frac{1}{x}=t

The equation  \frac{7}{2x}-  \frac{5}{2x}= \frac{20}{3x}+10  becomes \frac{7}{2}t- \frac{5}{2}t= \frac{20}{3}t+10

\frac{7}{2}t- \frac{5}{2}t= \frac{20}{3}t+10\\ \\ \Rightarrow \frac{7}{2}t- \frac{5}{2}t -\frac{20}{3}t=10\\ \\ \Rightarrow  \frac{7t \times 3-5t \times 3-20t \times 2}{6} =10\\ \\ \Rightarrow \frac{21t-15t-40t}{6} =10\\ \\ \Rightarrow -34t=10 \times 6=60\\ \\ \Rightarrow t=- \frac{60}{34}=- \frac{30}{17}  \\\\ \Rightarrow  \frac{1}{x}= - \frac{30}{17}  \\\\ \Rightarrow x= - \frac{17}{30}
2 5 2